Implementasi Prinsip-Prinsip Hukum Ekonomi Islam dalam Sistem Keuangan Negara - Savitri, Dewi; Muhammad Muchlis, Madian (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2024)
Significant progress has been made in Indonesia in the past several years to fortify and grow the Islamic finance industry as a vital component of the country's financial system. The purpose of this study is to investigate how the national financial system incorporates the tenets of Islamic economic law. The study uses a qualitative methodology and analyzes data from a range of sources, including scholarly publications. According to the findings, the national financial system adheres to the principles of Tawhid, fairness, perfection (Ihsan), responsibility (Mas'uliyah), moderation (Wasathiyah), and honesty as part of Islamic economic law. The incorporation of these concepts into the country's financial system yields noteworthy benefits in terms of social fairness, communal prosperity, economic empowerment, and corruption prevention.